Central venous catheter care interventions for preventing central line-associated bloodstream infections in adult intensive care units: A systematic review - Rycco Darmareja; Galuh Nurulita Fitriani; Nabilla Asmarany; Maulyda Azzahra (Universitas Airlangga, 2026)
Introduction: Central venous catheters (CVCs) are essential in the management of critically ill patients. However, their use may increase the risk of complications, particularly central line-associated bloodstream infections (CLABSIs). This systematic review aimed to evaluate evidence-based CVC care interventions for reducing the risk of CLABSIs in intensive care units. Methods: This review was conducted in accordance with the PRISMA 2020 guidelines. Specific keywords related to CVC care and CLABSI prevention were used to identify articles published between 2020 and 2024 in PubMed, ScienceDirect, and Google Scholar. A total of 48,541 records were identified and screened according to predefined criteria, including original research articles written in English and available in full text. Review articles, editorials, commentaries, abstract-only articles, and articles with restricted access were excluded. Nine articles met the eligibility criteria and were critically appraised using the Joanna Briggs Institute tool to assess the methodological quality of the included studies. Results: Daily bathing with 2% chlorhexidine, antisepsis of the insertion site using 1-2% chlorhexidine, timely dressing changes, polyhexamethylene biguanide (PHMB) dressings, and consistent adherence to central line care bundles were associated with reduced CLABSI incidence. Conclusions: These interventions emphasize the role of nurses in maintaining CVC care and preventing healthcare-associated infections. The implementation of evidence-based CVC care practices is therefore recommended to reduce the incidence of CLABSIs in the ICU.